2015
DOI: 10.1097/md.0000000000002002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Enhanced External Counterpulsation in Patients With Chronic Refractory Angina on Canadian Cardiovascular Society (CCS) Angina Class

Abstract: A growing number of patients with chronic artery disease suffer from angina, despite the optimal medical management (ie, β-blockers, calcium channel blockers, and long-acting nitrates) and revascularization. Currently, enhanced external counterpulsation (EECP) therapy has been verified as a noninvasive, safe therapy for refractory angina. The study was designed to evaluate the efficacy of EECP in patients with chronic refractory angina according to Canadian Cardiovascular Society (CCS) angina class.We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…EECP has beneficial effects and has been used as an additional alternative when conventional therapy has not been successful to adequate symptom control, but 15–30% of treated patients do not experience neither subjective nor objective clinical improvement 12,16,24 . Identification of potential responders to EECP before treatment initiation could be reasonable as the treatment is not widely available, it is relatively time and resource intensive and a significant proportion of patients do not experience benefit.…”
Section: Introductionmentioning
confidence: 99%
“…EECP has beneficial effects and has been used as an additional alternative when conventional therapy has not been successful to adequate symptom control, but 15–30% of treated patients do not experience neither subjective nor objective clinical improvement 12,16,24 . Identification of potential responders to EECP before treatment initiation could be reasonable as the treatment is not widely available, it is relatively time and resource intensive and a significant proportion of patients do not experience benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The MUST-EECP study was an RCT that showed EECP to be associated with a significant decrease in angina frequency amongst patients with RA, as well as an improvement in time to ST-segment depression on stress testing. 23 Subsequently, a number of studies have corroborated these findings, with meta-analyses demonstrating that use of EECP is associated with improvements in anginal symptom burden 24,25 and myocardial perfusion. 26 In addition to the multitude of studies demonstrating the symptomatic benefit of EECP, the technique is also of proven effectiveness in reducing hospital expenditure.…”
Section: Enhanced External Counterpulsation (Eecp)mentioning
confidence: 92%
“…По данным мета-анализов работ с оценкой среднесрочных эффектов УНКП у пациентов со стабильной ИБС, в т.ч. осложненной ХСН, положительный эффект (снижение функционального класса стенокардии минимум на 1 единицу) отмечен у 84-86% пациентов [15,16].…”
Section: материал и методыunclassified